Período puerperal: a importância da visita domiciliar para enfermeiros da Atenção Primária à Saúde - Leticia dos Santos Medeiros; Ana Carla Marques da Costa (Universidade Federal do Ceará, 2016)
Objective: to understand the importance given by nurses working in primary health care for the realization of home visits in the puerperal period. Methods: qualitative research held with 38 nurses by applying a semistructured interview, in which the thematic content analysis technique was used under Bardin's theoretical light. Results: the majority of interviewees considered the home visit a tool that brings the health unit to the reality experienced by the mother, however, there are still many professionals who omit some precautions when dealing with this population. Conclusion: the home visit is considered essential for contributing to the reduction of morbidity and mortality of the postpartum and newborn, increasing the bond between unit and family, and reducing the risk of postpartum complications, however, the attention turned to these women is still covered with big challenges to achieve a real satisfactory assistance.